The Fair Administration Building, New York World's Fair (Curt Teich & Co.)
The Administration Building of the New York World's Fair is air-conditioned, scientifically designed and modern in every respect. The sculpture by Albert Stewart adorning the facade represents "Mithrana" above the towers of Manhattan. Her gesture is one of welcome.